Bridging gender gaps through innovations in agricultural value chains in Africa - Njiraini, G.; Ngigi, M. (IAAE, 2018)
This paper examines innovations for bridging gender gaps in agricultural value chains in Africa. It focuses on innovative platforms for addressing gender gaps, considering women contribute up to 40 percent of labor in agricultural production. Women remain at the bottom of value chains and face gender-specific constraints attributable to gender and social norms, discriminatory beliefs and practices, gender-blind designs and delivery of technologies and innovations which impede women’s participation in value chains. Consequently, women are unable to adjust to challenges and opportunities of technological progress, commercial orientation, and global integration. This paper suggests that gender-sensitive technological and institutional innovations is essential to promote women’s participation in agricultural value chains and bridge the gender gap while upholding gender-specific outcomes. The study shows that women rely on alternative institutional innovations and arrangements such as group-based approaches in order to improve their participation in value chains which implies the call for policies that nurture and strengthen these kinds of institutions. Integrating research, designing value chain interventions and monitoring and evaluation with a gender lens is essential in order to accelerate women’s participation in value chain development programmes, while allowing them to be role models and spearhead their own empowerment.
Keywords: Gender gaps; Gender-sensitive innovations; Agricultural value chains,; Africa